A collaborative exercise on DNA methylation-based age prediction and body fluid typing. (March 2022) - Lee, Ji Eun; Lee, Jeong Min; Naue, Jana; Fleckhaus, Jan; Freire-Aradas, Ana; Neubauer, Jacqueline; Pośpiech, Ewelina; McCord, Bruce; Kalamara, Vivian; Gauthier, Quentin; Mills, Carly; Cao, Yijian; et al.
Abstract: DNA methylation has become one of the most useful biomarkers for age prediction and body fluid identification in the forensic field. Therefore, several assays have been developed to detect age-associated and body fluid-specific DNA methylation changes. Among the many methods developed, SNaPshot-based assays should be particularly useful in forensic laboratories, as they permit multiplex analysis and use the same capillary electrophoresis instrumentation as STR analysis. However, technical validation of any developed assays is crucial for their proper integration into routine forensic workflow. In the present collaborative exercise, two SNaPshot multiplex assays for age prediction and a SNaPshot multiplex for body fluid identification were tested in twelve laboratories. The experimental set-up of the exercise was designed to reflect the entire workflow of SNaPshot-based methylation analysis and involved four increasingly complex tasks designed to detect potential factors influencing methylation measurements. The results of body fluid identification from each laboratory provided sufficient information to determine appropriate age prediction methods in subsequent analysis. In age prediction, systematic measurement differences resulting from the type of genetic analyzer used were identified as the biggest cause of DNA methylation variation between laboratories. Also, the use of a buffer that ensures a high ratio of specific to non-specific primer binding resulted in changes in DNA methylation measurement, especially when using degenerate primers in the PCR reaction. In addition, high input volumes of bisulfite-converted DNA often caused PCR failure, presumably due to carry-over of PCR inhibitors from the bisulfite conversion reaction. The proficiency of the analysts and experimental conditions for efficient SNaPshot reactions were also important for consistent DNA methylation measurement. Several bisulfite conversion kits were used for this study, but differences resulting from the use of any specific kit were not clearly discerned. Even when different experimental settings were used in each laboratory, a positive outcome of the study was a mean absolute age prediction error amongst participant's data of only 2.7 years for semen, 5.0 years for blood and 3.8 years for saliva. Highlights: Technical validation of DNA methylation-based age prediction and body fluid typing in 12 laboratories. Body fluid typing from each laboratory provided sufficient information to determine appropriate age prediction methods. Even with different experimental settings, mean absolute age prediction -errors were 5.0 years or less. Genetic analyzer type, PCR buffer composition and bisulfite-converted DNA volume can affect DNA methylation measurement. DNA methylation variation can be better controlled by harmonizing experimental conditions and improved technical training.